Prinsip – Prinsip Good Governance dalam Pemerintahan Dinasti Umayyah (Kajian Pada Masa Pemerintahan Islam : Muawiyah Bin Abu Sufyan 661-668 SM) - Amaliatulwalidain Amaliatulwalidain (UNIVERSITAS INDO GLOBAL MANDIRI, 2019)
AbstractThe study in this paper is to discuss the principles of good governance applied in the administration system of Islamic governance in the Umayyad dynasty in Shia (Damascus) especially during the Muawiyah period of Bin Abu Sufyan. It is very interesting to study more deeply in the Umayyad administration system during the period of Muawiyah ibn Abu Sufyan's leadership, there was a major breakthrough in his administration with the open concept of Roman (Byzantium) Muawiyah Bin Abu Sufyan pioneering and pioneering the birth of the first bureaucratic system and state system in the history of civilization in Islamic government in the world. The bureaucratic system and the government system of the government of Muawiyah Bin Abu Sufyan, later became a reference for the system of Islamic governance in the future even today. The system of government during the Muawiyah bin Abu Sufyan period was in general and structured. For the sake of creating a good and directed governance system, several government departments (bureaucracy) and state institutions with different tasks, roles and functions for each department. The presence of the bureaucratic system and the government system is very helpful in the governance process, including the bureaucratic system, namely office work (postal correspondence), departmental stamps, transportation offices, secretarial offices, financial offices and trade watch offices, while the government system is implemented with a guard office and police station.Keywords: Good Governance, Ummayah Dynasty Government System, Muawiyah Bin Abu SufyanAbstrakStudi dalam tulisan ini adalah membahas mengenai prinsip-prinsip pemerintahan yang baik (good governance ) yang diterapkan dalam sistem administrasi pemerintahan Islam pada dinasti Umayyah di Syiah (Damaskus) khususnya selama periode kepemimpinan Muawiyah Bin Abu Sufyan. Sangat menarik untuk dikaji lebih dalam lagi bahwa dalam sistem administrasi Umayyah pada periode kepemimpinan Muawiyah bin Abu Sufyan, telah terjadi terobosan besar pada pemerintahannya denga mengadopsi konsep pemerintahan dari Romawi (Byzantium) Muawiyah Bin Abu Sufyan telah merintis dan mempelopori lahirnya sistem birokrasi dan sistem keamanan negara pertama dalam sejarah peradaban pemerintahan Islam di dunia. Bahkan sistem birokrasi dan sistem institusi keamanan dari pemerintahan Muawiyah Bin Abu Sufyan, kemudian menjadi acuan bagi sistem pemerintahan Islam dikemudian hari bahkan hingga saat ini. Sistem pemerintahan selama periode kepemimpinan Muawiyah bin Abu Sufyan dikelola secara teratur dan terstruktur. Demi menciptakan sistem pemerintahan yang baik dan terarah, beberapa departemen pemerintah (birokrasi) dan lembaga keamanan negara dibentuk dengan pembagian tugas, peran dan fungsi yang jelas bagi masing-masing departemen. Kehadiran dari sistem birokrasi dan sistem keamanan tersebut secara sistematis sangat membantu dalam proses pemerintahan, diantara dari sistem birokrasi tersebut,di antaranya adalah kantor pos (korespondensi pos), stempel departemen, kantor transportasi, kesekretariatan, kantor keuangan dan kantor pengawas perdagangan, sedangkan sistem keamanan diimplementasikan dengan kantor pengawal dan kantor polisi.Kata kunci: Good Governance, Sistem Pemerintahan Dinasti Ummayah, Muawiyah Bin Abu Sufyan